Vector Form Intrinsic Finite Element Method for Dynamic Response Analysis of Deep-Sea Mining Hose - Jingchang Xu; Xiaoyan Li; Hao Zheng; Honghao Yan; Ming Zhang; Bingkun Wang (Journal of Marine Science and Engineering)
The deep-sea mining hose is a crucial component of the underwater lifting and transport system utilized in deep-sea mining operations. The marine environmental loading and the dynamic coupling between the hose, the subsea mining vehicle, and the relay bin have a complex effect on the mechanical properties of the hose. This study employs the vector form intrinsic finite element method to develop a MATLAB-based three-dimensional dynamic response simulation program for analyzing the hose’s dynamic response characteristics under varying current velocities, buoyancy module quantities, relay bin resonance conditions, and mining vehicle motions with double-hose systems, etc. The findings demonstrate that the vector form intrinsic finite element method effectively simulates the dynamic behavior of the hose structure. It is necessary to analyze the dynamic response of the hose’s multiple factors.